THE GSM STANDARD MOBILE TELECOMMUNICATION SYSTEM FOR AIRSPACE RADAR CONTROL NEEDS - Vadym I. Sliusar; Andrii O. Zinchenko; Kateryna A. Zinchenko (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In the article identified a tendency of combined platforms hardware tools radiofrequency and digital signal processing for general solution communication and radiolocation tasks. The analysis of developments in the application of mobile communication of GSM standard to solving problems for airspace radar control. An analysis of developments in the area of the use of mobile communication GSM standard for solving problems of radiolocation control of airspace were made. Investigated the use of digital technology of beam forming to detect air targets with the help of mobile communication systems. Presented the results of research upper limit radio emission cellular communication systems. Appropriate researches were made by the authors during an ordinary regular flights of passenger airliners, using smartphone IPhone 5S, which was switched on mode satellite navigation to determine the current flight altitude and location coordinates. At the same time on the display of smartphone was monitored indication of presence connection with terrestrial cellular base stations appropriate for that or another locality operator communication services. Substantiated creating air space control system for the needs of special users Ukraine based on existing GSM networks.